Pengaruh penerapan E-SPT, pengetahuan dan sosialisasi perpajakan terhadap kepatuhan wajib pajak orang pribadi - Mahpudin, Endang; Ikhsan, Sugiyanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to ascertain and evaluate the impact of E-SPT Implementation, Knowledge, and Socialization on Personal Taxpayer Compliance in TelukJambe Village. A questionnaire-based primary data set was used in the study, which employed quantitative methodologies. 620 persons participated in the study's population. In this study, 86 respondents made up the sample. Purposive sampling is the sampling method employed. The findings revealed that Socialization had no major impact on people's tax payer compliance, knowledge had a substantial impact, and the implementation of E-SPT had no significant impact on taxpayer compliance. E-spt, knowledge, and socialization all have an impact on tax payer compliance.